THE MISSING PIECE OF ADULT HYPOPHOSPHATEMIC RICKETS PUZZLE: A CASE REPORT OF SUSPECTED X-LINKED HYPOPHOSPHATEMIA (XLH) WITH RECURRENT DENTAL ABSCESS - MM, Nur Hidayah; R, Teh Roseleen Nadia (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND X-linked Hypophosphatemia (XLH) is associated with primary musculoskeletal complications and can present with recurrent dental-related complications. CASE We present a case of poorly treated XLH who not only presented with typical bone deformities but also with overlooked dental complications. A 24-year-old female presented to us with short stature, severe bowing of the legs with leg pain, frontal bossing, and bilateral genu varus with recurrent dental-related problems requiring multiple visits to the dentist, causing distress as she is losing her teeth. She had undergone an osteotomy four times on her left femur. Family history was insignificant. Assessment by the dentist reveals multiple cyst and abscess formations at both the upper and lower jaws and malocclusion. She has normal calcium (2.18 mmol/L), low phosphate (0.47 mmol/L) with low Renal-Tubular-Reabsorptionof-Phosphate (TMP/GFR) [0.67 mmol/L] and vitamin D deficiency (35 nmol/L). No evidence of other renal electrolytes or acid-base loss was noted. Her intact PTH and ALP were normal. Serum calcium, phosphate, and vitamin D levels improved with Sandoz phosphate 500 mg given twice daily, alphacalcidol 1 mg once daily, and calcium carbonate 500 mg twice daily. Her latest serum calcium was 2.39 mmol/L, serum phosphate increased to 0.71 mmol/L, vitamin D level likewise improved to 88.9 nmol/L, and iPTH was normal 27.7 pg/ml (14.9–56.9). Ultrasound of the kidneys did not show any medullary nephrocalcinosis. No confirmatory genetic tests to look at PHEX mutation gene were done due to financial constraints. CONCLUSION Adult XLH can present with only dental-related issues and are often overlooked. It can lead to premature tooth loss, resulting in adverse practical, cosmetic, and social sequelae. Hence, dental-related complaints should always be addressed and treated. Studies have shown that dental issues are milder among people who underwent conventional therapy compared to those who did not receive continuous treatment. Supplementation with phosphorus and a vitamin D analogue enhances the mineralization of dentin and decreases the frequency of dental abscesses.